Cheirostylis wenshanensis, a new species of Orchidaceae from Yunan, China - Chen, Gui-Zhen; Chen, Li-Jun; Rao, Wen-Hui; Zheng, Fang; Liu, Wei-Rong; Zhang, Pei-Wen; Chen, Jian-Bing (Phytotaxa, 2019)
A new orchid species, Cheirostylis wenshanensis (Orchidaceae; Cranichideae; Goodyerinae), from Yunnan Province, China, is described and illustrated based on morphological. This new species is similar to C. pingbianensis, but it differs by having a leaf-like flora bract at bottom, to 2.3 cm long; Inflorescence raceme with 5 flowers; The rest part of lateral sepal 2.8–3 mm, front of lip 5–6 × 5–6 mm, both with 1 pale green spot at base of lip lobes, without denticulate between lobes.